“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

The role of electromagnetic interactions in second harmonic generation from plasmonic metamaterials - Alberti, Julian; Linnenbank, Heiko; Linden, Stefan; Grynko, Yevgen; Förstner, Jens (Applied Physics B)
We report on second harmonic generation spectroscopy on a series of rectangular arrays of split-ring resonators. Within the sample series, the lattice constants are varied, but the area of the unit cell is kept ﬁxed. The SHG signal intensity of the different arrays upon resonant excitation of the fundamental plasmonic mode strongly depends on the respective arrangement of the split-ring resonators. This ﬁnding can be explained by variations of the electromagnetic interactions between the split-ring resonators in the different arrays. The experimental results are in agreement with numerical calculations based on the discontinuous Galerkin time-domain method. (PDF) The role of electromagnetic interactions.... Available from: https://www.researchgate.net/publication/297612326_The_role_of_electromagnetic_interactions_in_second_harmonic_generation_from_plasmonic_metamaterials [accessed Aug 13 2018].
Keywords: tet_topic_shg; tet_topic_meta

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

A versatile design for resonant guided-wave parametric down-conversion sources for quantum repeaters - Brecht, Benjamin; Luo, Kai-Hong; Herrmann, Harald; Silberhorn, Christine (Applied Physics B)

Coherent photocurrent spectroscopy of single InP-based quantum dots in the telecom band at 1.5 µm - Gordon, S.; Yacob, M.; Reithmaier, J. P.; Benyoucef, M.; Zrenner, Artur (Applied Physics B)
In this work we study the resonant and coherent properties of single InP-based InAs quantum dots, which show an optical emission in the telecom C-band and L-band. High-resolution resonant photocurrent spectroscopy on p–i–n devices reveals narrow linewidths and fully resolved fine structure splittings. We observe Lorentzian line shapes, which allow for the extraction of dephasing times as a function of the applied bias voltage. Coherent ps laser excitation results in pronounced Rabi rotations with increasing pulse area. For π-pulse excitation, we obtain more than 93 % of the theoretically expected photocurrent amplitude. Our results also demonstrate that such state-of-the-art InP-based quantum dots for the telecom band exhibit promising key parameters comparable to well-established InAs/GaAs counterparts.
Keywords: Bias Voltage; Optical Parametric Oscillator; Molecular Beam Epitaxy Growth; Internal Electric Field; Dephasing Time

Quantum technology: from research to application - Schleich, Wolfgang P.; Ranade, Kedar S.; Anton, Christian; Arndt, Markus; Aspelmeyer, Markus; Bayer, Manfred; Berg, Gunnar; Calarco, Tommaso; Fuchs, Harald; Giacobino, Elisabeth; Grassl, Markus; Hänggi, Peter; et al. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

Towards a quantum interface between telecommunication and UV wavelengths: design and classical performance - Rütz, Helge; Luo, Kai-Hong; Suche, Hubertus; Silberhorn, Christine (Applied Physics B)

A versatile design for resonant guided-wave parametric down-conversion sources for quantum repeaters - Brecht, Benjamin; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine (Applied Physics B)

Simulations of high harmonic generation from plasmonic nanoparticles in the terahertz region - Grynko, Yevgen; Zentgraf, Thomas; Meier, Torsten; Förstner, Jens (Applied Physics B)
Keywords: tet_topic_meta; tet_topic_shg

Quantum interference control of electrical currents in GaAs microstructures: physics and spectroscopic applications - Sternemann, E.; Jostmeier, T.; Ruppert, C.; Thunich, S.; Duc, H. T.; Podzimski, R.; Meier, Torsten; Betz, M. (Applied Physics B)

Advanced optical manipulation of carrier spins in (In,Ga)As quantum dots - Varwig, S.; Evers, E.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Meier, Torsten; Zrenner, Artur; Bayer, M. (Applied Physics B)
Spins in semiconductor quantum dots have been considered as prospective quantum bit excitations. Their coupling to the crystal environment manifests itself in a limitation of the spin coherence times to the microsecond range, both for electron and hole spins. This rather short-lived coherence compared to atomic states asks for manipulations on timescales as short as possible. Due to the huge dipole moment for transitions between the valence and conduction band, pulsed laser systems offer the possibility to perform manipulations within picoseconds or even faster. Here, we report on results that show the potential of optical spin manipulations with currently available pulsed laser systems. Using picosecond laser pulses, we demonstrate optically induced spin rotations of electron and hole spins. We further realize the optical decoupling of the hole spins from the nuclear surrounding at the nanosecond timescales and demonstrate an all-optical spin tomography for interacting electron spin sub-ensembles.
Keywords: Spin Polarization; Pump Pulse; Trion; Spin Component; Coherence Time

Liquid-nitrogen cooled, free-running single-photon sensitive detector at telecommunication wavelengths - Covi, M.; Pressl, B.; Günthner, T.; Laiho, K.; Krapick, Stefan; Silberhorn, Christine; Weihs, G. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Atmospheric channel characteristics for quantum communication with continuous polarization variables - Heim, B.; Elser, D.; Bartley, Tim; Sabuncu, M.; Wittmann, C.; Sych, D.; Marquardt, C.; Leuchs, G. (Applied Physics B)

Electromagnetic induction in metamaterials - Meyrath, T. P.; Zentgraf, Thomas; Rockstuhl, C.; Giessen, H. (Applied Physics B)

Influence of particle size and concentration on the second-harmonic signal generated at colloidal surfaces - Schneider, L.; Schmid, Hans-Joachim; Peukert, W. (Applied Physics B)
Second harmonic generation (SHG) spectroscopy is a recently developed technique for the investigation of surface properties of particles. To apply the method to technical colloidal systems, the dependences of several experimental parameters on the signal have to be studied. In this work the influence of particle concentration on the SHG signal from the surfaces of colloids (polystyrene beads in a size range of 0.1 μm to 2.9 μm) is investigated. A simple model, based on Lambert–Beer’s law, to describe the measured dependences is derived. The model agrees with the experimental observations for particles smaller 1.1 μm and with a small modification also for larger particles. Based on the new model an analytical equation for determining the optimum concentration, where highest signals in colloidal SHG spectroscopy measurements are obtained, is derived.

Optical switching in metallic photonic crystal slabs with photoaddressable polymers - Nau, D.; Bertram, R.P.; Buse, K.; Zentgraf, Thomas; Kuhl, J.; Tikhodeev, S.G.; Gippius, N.A.; Giessen, H. (Applied Physics B)

Resonances of split-ring resonator metamaterials in the near infrared - Rockstuhl, C.; Zentgraf, Thomas; Guo, H.; Liu, N.; Etrich, C.; Loa, I.; Syassen, K.; Kuhl, J.; Lederer, F.; Giessen, H. (Applied Physics B)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)

Optical storage effect in a platinum orthometalated liquid crystal - Buey, J.; Díez, L.; Espinet, P.; Kitzerow, Heinz-Siegfried; Miguel, J.A. (Applied Physics B: Lasers and Optics)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

Storage of laser-induced holographic gratings in discotic liquid crystals - Contzen, J.; Heppke, G.; Kitzerow, Heinz-Siegfried; Krüerke, D.; Schmid, H. (Applied Physics B Laser and Optics)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering